Revealing the transitory and local effect of zebularine on development and on proteome dynamics of Salix purpurea - Pagano, Andrea; Gomes, Carolina; Timmerman, Evy; Sulima, Paweł; Przyborowski, Jerzy Andrzej; Kruszka, Dariusz; Impens, Francis; Paiva, Jorge Almiro Pinto (Frontiers in Plant Science, 2024)
Introduction DNA methylation plays major roles in the epigenetic regulation of gene expression, transposon and transcriptional silencing, and DNA repair, with implications in developmental processes and phenotypic plasticity. Relevantly for woody species, DNA methylation constitutes a regulative layer in cell wall dynamics associated with xylogenesis. The use of methyltransferase and/or demethylase inhibitors has been proven informative to shed light on the methylome dynamics behind the regulation of these processes. Methods The present work employs the cytidine analog zebularine to inhibit DNA methyltransferases and induce DNA hypomethylation in Salix purpurea plantlets grown in vitro and in soil. An integrative approach was adopted to highlight the effects of zebularine on proteomic dynamics, revealing age-specific (3 weeks of in vitro culture and 1 month of growth in soil) and tissue-specific (stem and root) effects. Results and discussion After 3 weeks of recovery from zebularine treatment, a decrease of 5-mC levels was observed in different genomic contexts in the roots of explants that were exposed to zebularine, whereas a functionally heterogeneous subset of protein entries was differentially accumulated in stem samples, including entries related to cell wall biosynthesis, tissue morphogenesis, and hormonal regulation. Significant proteomic remodeling was revealed in the development from in vitro to in-soil culture, but no significant changes in 5-mC levels were observed. The identification of tissue-specific proteomic hallmarks in combination with hypomethylating agents provides new insights into the role of DNA methylation and proteome in early plant development in willow species. Proteomic data are available via ProteomeXchange with identifier PXD045653. WGBS data are available under BioProject accession PRJNA889596.